Edaravone Injected at the Start of Reperfusion Suppresses Myonephropathic Metabolic Syndrome in Rats - Yamamura, Mitsuhiro; Miyamoto, Yuji; Mitsuno, Masataka; Tanaka, Hiroe; Ryomoto, Masaaki (International Journal of Angiology, 2014)
The purpose of this study was to evaluate whether edaravone (Radicut®, Mitsubishi Tanabe Pharma Co., Osaka, Japan) injected at the start of reperfusion can suppress myonephropathic-metabolic syndrome (MNMS). MNMS models were made by clamping the bilateral common femoral arteries for 5 hours. At de-clamping (at the start of reperfusion), they were intra-peritoneal injected with 9.0 mg/kg of edaravone (the edaravone group, n = 5) or an equal volume of saline (the control group, n = 5). At five hours after de-clamping, the lower extremity muscles were stained with hematoxylin & eosin (H&E) to count the viable cells, and periodic acid- Schiff (PAS) to assess the glycogen storage. The lungs were also stained with H&E to expresse the alveolar wall thickness, and naphthol AS-D chloroacetate esterase to label infiltrating active neutrophils.The viable muscle cells in the edaravone group was significantly greater than that of the control group (593 ± 60 vs. 258 ± 31 cells/mm2, p < 0.01). The PAS-positive area in the edaravone group was also significantly higher than that in the control group (30.1 ± 6.9 vs. 7.3 ± 2.1%, p < 0.001). The alveolar wall thickness in the edaravone group was significantly lower than that in the control group (63.6 ± 5.6 vs. 17.2 ± 5.2%, p < 0.001). The active neutrophil infiltration in the edaravone group was also significantly lower than that in the control group (249 ± 59 vs. 68 ± 8 cells/mm2, p < 0.001).We conclude that edaravone injected at the start of reperfusion can suppress not only muscle reperfusion injury but also lung damage.
Keywords: myonephropathic metabolic syndrome; reperfusion injury; free radical; edaravone (Radicut)